2013
DOI: 10.5812/nms.8518
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Quality of Life and Depression in Pregnant Women

Abstract: Results:The findings showed that there was an inverse relationship between quality of life and depression in pregnancy (P = 0.0001). Average scores in all eight domains of quality of life were significantly lower in depressed pregnant women compared to nondepressed women. The strongest relationship was observed between depression and vitality (r =-0.52, P = 0.0001), mental health (r = -0.50, P = 0.001) and social functioning (r =-0.38, P = 0.001). Conclusion: Depressed pregnant women had a lower quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…Although pregnancy is a normal physiological event, it signifies important changes in a woman’s life, and necessitates her adaptation to these changes (1). According to Kiehl et al women’s adaptation to motherhood roles during pregnancy positively affects their self-confidence and life satisfaction in the postpartum period (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although pregnancy is a normal physiological event, it signifies important changes in a woman’s life, and necessitates her adaptation to these changes (1). According to Kiehl et al women’s adaptation to motherhood roles during pregnancy positively affects their self-confidence and life satisfaction in the postpartum period (2).…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Saqqez, this figure was 62.9±15.3 in healthy pregnant women and 53.2±11.8 in women with restless leg syndrome (Ghanei Gheshlagh, Toloeipoor Lanjavani, Lazari, & Moslemi, 2014). In their other study in Kashan, Abbasszadeh et al reported the mean score of quality of life as 63.72±12.86 in non-depressed pregnant women and as 52.85±11.8 in depressed pregnant women (F. Abbaszadeh et al, 2013). …”
Section: The Mean Score Of Quality Of Lifementioning
confidence: 99%
“…In contrast, factors such as prenatal mental disorders (F. Abbaszadeh et al, 2013;Mirmohammadaliei et al, 2007;Mortazavi et al, 2014;S. Shishehgar et al, 2013), the severity of pregnancy nausea and vomiting (Jouybari L et al, 2012;F.…”
Section: Factors Associated With Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which SF-36 was used on two different groups of pregnant women with and without depression, it was found that the pregnant women had poor life quality scores. It was determined that the life qualities and especially "mental health", "vitality" and "social function" sub-dimensions of pregnant women who are diagnosed with depressive disorder were much worse (34). Sleep quality and life quality were found to be inversely related in many fields.…”
Section: Discussionmentioning
confidence: 99%